Fast boys and pretty girls : a novel - Patrick, Lo (Sourcebooks Landmark, 2025)
"Following a semi-successful career as a teen model in New York City, Danielle Greer has moved back to the mountains of North Georgia and is living in her childhood home with her husband and four daughters. One stifling, lazy afternoon, the girls are exploring the ravine behind the house when they come across a body"--